DEVELOPING READING MATERIALS FOR THE ELEVENTH GRADE STUDENTS OF INFORMATION TECHNOLOGY PROGRAM OF SMK GAJAH MADA MEDAN - Fariza Yusrizal and Nora Ronita Dewi (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This research was aimed to develop the appropriate reading materials for the eleventh grade students of Information Technology Program of SMK Gajah Mada Medan. Due to the result in the form of a product, this study was categorized as Research and Development (R & D) study which adapted from Borg and Gall (1989) theory with some modifications. The subject of this study was the eleventh grade students of Information Technology Program of SMK Gajah Mada Medan. In conducting this research, the procedures were gathering the data and information, conducting the need analysis, designing the first draft of materials, validating by the experts, revising the materials, and producing the final product. The instruments of collecting data were the combination of two strategies; interview and questionnaires. The interview result was analyzed as qualitative data and the questionnaires analyzed as quantitative data. These data were needs of students covering target needs and learning needs. This study developed reading materials which only focused on procedure text taught in the even semester. These materials were based on Curriculum 2013.